Study protocol for a mixed-methods pilot of a physiotherapy plus education program for inpatients with major depressive disorder: Feasibility and preliminary effects - José Lesmes Poveda-López; Carolina Jiménez-Sánchez; Raquel Lafuente-Ureta; Bárbara Marco-Gómez; Ana Villagrasa-Cantín; Sara Pérez-Mansilla; Marta Guarch-Rubio; Juan Francisco Roy (PLoS ONE, 2025)
Background Major depressive disorder is a mood disorder with significant psychological and physical symptoms that can lead to disability and other severe consequences. This disorder is influenced by both genetic and environmental factors, causing neurotransmitter imbalances and inflammation. Given mayor depressive disorder’s high prevalence and impact, it is crucial to implement a health promotion and intervention program aimed at this disorder. Investigating the feasibility of physical therapy, including therapeutic exercise and health education, compared to psychiatric and psychological approaches is an essential component of this program and of improving the quality of life for patients affected by mayor depressive disorder. Methods A concurrent nested mixed-methods study with quantitative dominance will be conducted. The quantitative study will be a quasi-experimental pilot study with a pre-post design. This study will additionally include a qualitative narrative design. Initial and post-intervention evaluations will include sociodemographic and clinical data. Quantitative data will be collected using the EQ-5D-3L, MADRS, NRS, GSE, and GCPC-UN-ESU questionnaires. These tools assess health status, depression severity, pain intensity, self-efficacy, and satisfaction levels. Qualitative data will be collected from focus groups with 6–8 participants. The question guide for patients will cover their experiences with their illness and intervention, while the guide for professionals will cover their perceptions of patient management and observed barriers and facilitators. All participants will receive the same evidence-based intervention over 3–6 weeks, with 2 weekly sessions of approximately 45 minutes each. Each session will consist of therapeutic exercise and health education to improve patients’ physical condition and self-management skills. Discussion This study aims to evaluate the feasibility and acceptability of a physiotherapy intervention program for MDD patients. It will also provide preliminary insights into the effects on quality of life, pain, and self-efficacy, which will inform the design of a future definitive trial. The findings from this research will provide valuable scientific insights and a basis for guiding health-care policymakers on the potential inclusion of physical therapy in clinical practice guidelines and standard hospital treatments for major depressive disorders. Clinical Trial registration NCT06983405.